2020
DOI: 10.3389/fcell.2020.00407
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Neurogenesis in Germ-Free Mice: Effects of Age and Sex

Abstract: The gut microbiome has profound effects on development and function of the nervous system. Recent evidence indicates that disruption of the gut microbiome leads to altered hippocampal neurogenesis. Here, we examined whether the effects of gut microbiome disruption on neurogenesis are age-dependent, given that both neurogenesis and the microbiome show age-related changes. Additionally, we examined memory induced functional connectivity of hippocampal networks. Control and germ-free mice at three different ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 51 publications
(75 reference statements)
3
44
0
1
Order By: Relevance
“…Previous studies aimed at assessing the impact of microbes on hippocampal neurogenesis have revealed somewhat differing results, possibly due to different experimental conditions and timelines for monitoring neurogenesis. For instance, in one study, a different mouse line (Swiss Webster) was used (66), whereas in another, hippocampal neurogenesis was assessed earlier in life (58). A third study reported a decrease in adult neurogenesis of adult male C57BL/6J mice after antibiotic treatment (67), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies aimed at assessing the impact of microbes on hippocampal neurogenesis have revealed somewhat differing results, possibly due to different experimental conditions and timelines for monitoring neurogenesis. For instance, in one study, a different mouse line (Swiss Webster) was used (66), whereas in another, hippocampal neurogenesis was assessed earlier in life (58). A third study reported a decrease in adult neurogenesis of adult male C57BL/6J mice after antibiotic treatment (67), which is consistent with our results.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, reducing systemic inflammation through modulation of the microbiome might be a strategy to increase neurogenesis. A recent study showed that alteration of the gut microbiome alters hippocampal neurogenesis in both an age-and sex-dependent manner, with young male germfree mice showing decreased hippocampal neurogenesis and increased neuron apoptosis (Scott et al, 2020). Gut microbiome from 2-year-old mice transplanted into 6-week-old germ-free mice increased the number of newborn hippocampal neurons and local BDNF expression in the short-term while the transplantation of microbiome from 6-week-old mice had no effect (Kundu et al, 2019).…”
Section: Alterations Of the Microbiomementioning
confidence: 99%
“…BrdU + and DCX + cells were counted following the instructions from the previous literature. 63 Quantification of BrdU and DCX is shown in Figures D and E, Figure 3A and Figure 3B show the mean fluorescence intensities of FPN1, which are displayed as the fold change normalized to the Fpn1 flox/flox group. Values are presented as the mean ± SD of three mice.…”
Section: Fpn1 Nestin-cko Mice Exhibit Brain Iron Deficiencymentioning
confidence: 99%